Peningkatan Literasi Administrasi Kesehatan Bagi Masyarakat Pengguna Layanan Rumah Sakit - Apriliani Apriliani; Lily Lily; Amel Kinanti Br.Purba; Andini Nurhasanah Parinduri; Athiya Zahra (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Digital transformation in hospitals has enhanced access to treatments; nonetheless, many individuals continue to encounter challenges in comprehending administrative procedures, engaging with the Social Security Agency, and utilizing digital services. This community service initiative seeks to enhance health administration literacy among the users of Malahayati Islamic Hospital in Medan, thereby fostering greater independence and accuracy in executing administrative procedures. The activity occurred in August 2025, aimed at patients and/or their accompanying families who were willing to engage in the program. The intervention methods encompassed community education via interactive counseling and discussions, dissemination of science and technology through concise guides/leaflets and video tutorials, training through reflective simulations on the utilization of hospital digital services, mediation to elucidate administrative barriers with pertinent units, and advocacy through recommendations for enhancing information services. The evaluation involved administering pre-tests and post-tests to 30 participants, with skill observation throughout the simulation and collection of participant feedback. The results demonstrated a substantial enhancement in knowledge post-intervention, with an average pretest score of 9.63 (SD 2.512) rising to 19.10 (SD 1.094), signifying an improvement in health administration literacy among the service users of Malahayati Islamic Hospital in Medan following the intervention. Hospital service users increased their awareness of necessary paperwork, the patient registration process for both new and existing patients, and developed enhanced confidence in utilizing digital services. This effort significantly enhanced health administration literacy and is advised to persist through ongoing education, mentoring for digitally disadvantaged populations, and the availability of readily accessible digital resources